A Cross-sectional Study of Fixed and Growth Mindset in Adult Peritoneal Dialysis Patients. (November 2021) - Fissell, Rachel B.; Schlundt, David; Cavanaugh, Kerri L.; Mueller, Claudia; Umeukeje, Ebele M.; Nair, Devika; Wild, Marcus; Chariwala, Saqib; Guide, Andrew; Stewart, Thomas; Wallston, Kenneth
Increasing home dialysis prevalence is an international priority. Many patients start peritoneal dialysis, then transition to hemodialysis after complications. New strategies are needed to support modality persistence. Health mindset refers to individual belief about capacity to change to improve health. Mindset was measured in a cross-section of 101 adult peritoneal dialysis patients from April 2019 to June 2020. The Health Mindset Scale was administered to characterize the continuum of fixed vs. growth mindset with respect to health. Health literacy and health self-efficacy were also assessed. Participants were 43% female, 32% African American, and 42% diabetic. Health mindset scores were skewed toward growth (range 3–18), with average (SD) 12.83 (4.2). Growth mindset was strongly associated with health self-efficacy. Adults receiving peritoneal dialysis report health mindset variation. Growth mindset and health self-efficacy correlation suggests measurement of similar constructs, demonstrating convergent validity. The Health Mindset Scale may identify individuals who could benefit from targeted interventions to improve mindset, and foster peritoneal dialysis modality persistence.